Sampling pleural nodules with an EBUS scope: A novel application. (2018) - Kassirer, Michael; Wiesen, Jonathan; Atlan, Karine; Avriel, Avital
Abstract: Convex endobronchial ultrasound transbronchial needle aspiration (C-EBUS-TBNA) has become an essential modality for diagnosis and staging of hilar, mediastinal, and central pulmonary lesions. A Trans-thoracic pleural biopsy is the accepted practice for diagnosing pleural nodules. However, the diagnostic yield of a pleural biopsy is limited and surgical procedures pose a greater risk. We report a unique case of using a C- EBUS scope for the diagnosis of pleural nodules and mediastinal lymph node metastasis in a man with metastatic renal cell carcinoma.